PERAMALAN INDEKS PEMBANGUNAN MANUSIA DI PROVINSI NUSA TENGGARA TIMUR DENGAN METODE DOUBLE EXPONENTIAL SMOOTHING DARI BROWN - Virgilius Daton Balamakin; Maryo Yoseph Ambarto Dwi Sili Osan Osan (Badan Pusat Statistik Provinsi NTT, 2025)
Introduction/Main Objectives: This study aims to forecast the Human Development Index (HDI) of East Nusa Tenggara Province (NTT) for the next five years using the Double Exponential Smoothing (DES) method, in order to provide an overview of HDI development as a basis for regional development planning. Background Problems: Although NTT's HDI has shown an upward trend over the past five years, its value remains relatively low nationally, ranking third lowest after Papua and West Papua. This lag is attributed to low per capita expenditure, education levels, and life expectancy. The COVID-19 pandemic in 2020 also temporarily reduced the HDI value. Novelty: This study employs the DES method to project NTT's HDI using optimal parameters estimated from historical data, providing accurate data-based predictions that can be directly utilized as a reference for human development policies at the provincial level. Research Methods: This study uses secondary data on NTT's HDI for the period 2010–2024 from the Central Statistics Agency. Time series analysis was performed using the DES method, estimating the parameters α and β, and measuring the accuracy of the model using SSE, MSE, RMSE, and MAPE. Findings/Results: The DES model with α = 1 and β = 0.1655 produced a MAPE of 0.421, indicating high accuracy. The forecasting results predict that the NTT HDI will increase from 68.03 in 2025 to 70.57 in 2029, reflecting continuous improvement in the dimensions of education, health, and living standards.